2008
DOI: 10.1111/j.1365-2672.2007.03626.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the Bacillus subtilis antimicrobial peptide subtilosin from the dairy product-derived Bacillus amyloliquefaciens

Abstract: This is the first report of intra-species horizontal gene transfer for subtilosin and the first fully characterized bacteriocin isolated from B. amyloliquefaciens. Finally, this is the first report on subtilosin's activity against bacterial vaginosis-associated pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
139
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(144 citation statements)
references
References 32 publications
3
139
0
2
Order By: Relevance
“…The only fully characterised bacteriocin from B. amyloliquefaciens was found to correspond to subtilosin A, a bacteriocin previously reported in B. subtilis [24]. However, genetic evidence suggests that this results rather from an intra-species horizontal transfer of gene (HGT) than from a mechanism selected by evolution.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The only fully characterised bacteriocin from B. amyloliquefaciens was found to correspond to subtilosin A, a bacteriocin previously reported in B. subtilis [24]. However, genetic evidence suggests that this results rather from an intra-species horizontal transfer of gene (HGT) than from a mechanism selected by evolution.…”
Section: Discussionmentioning
confidence: 76%
“…These include subtilin from B. subtilis [17], megacin A-216 from B. megaterium [16], cerein 7 from B. cereus [4] and subtilosin A, produced by some strains of both B. subtilis and B. amyloliquefaciens [3,4,24]. Some of these substances have been successfully tested as food preservatives in dairy products [4].…”
Section: Introductionmentioning
confidence: 99%
“…The lipopeptides could also induce the plant defence responses to conquer the pathogens . Moreover, some peptides were also reported to be able to inhibit the pathogen growth, such as lantibiotics, bacteriocin, and LCI protein (Sutyak et al 2008;Herzner et al 2011;Meng et al 2012;Arguelles Arias et al 2013;Scholz et al 2014;Rasimus-Sahari et al 2015). The good stability and inhibitory activities of the peptides pointed out their potential in the plant protection and food preservation.…”
mentioning
confidence: 99%
“…Subtilosin A is a 35-amino-acid bacteriocin originally isolated from Bacillus subtilis by Babasaki et al (2) but was also found in Bacillus atrophaeus (26) and Bacillus amyloliquefaciens isolated from a dairy product (29). It is a unique macrocyclic bacteriocin in part due to its having an anionic nature unlike many other membrane-targeting cationic bacteriocins.…”
mentioning
confidence: 99%